E-Learning: Introduction To Personal Computers/ Anwar Ahmad - Anwar, Ahmad (2001)
WXES3182 is the final year project which involves doing a thesis. The purpose of doing this thesis is to apply the techniques learned during classes. The Final result of the thesis is to produce complete software. To actually produce the software, a development process will have to be followed through. Here application of the development phases are put to use such as analysis, design and implementation. In the first part of the thesis WXES3182, development in started and carried through up until design phase. WXES3182 will continue the development process until the completed product is produces. Software developmet phases such as requirements, analysis and specification have been carried through the process of writing this report. Technology has advance are rapidly in the past few years and many new technologies have sprung up. Computer are now being used very often yet very few people know how to use it well. With that in mind, I have set out to make educational software that will hopefully be able to educate people about the personal computers and promote better use of them. The Software will incorporate multimedia elements and interactivity to facilitate the learning process. This software is tiled E-Learning: An introduction to Personal Computer. It is hoped that with the use of this software, more people will be able to better utilize their computers.